RACE: the role of anchor characteristics in e-commerce success - Huo, Shao Hua; Wan Abas, Wan Anita; Waheed, Moniza (Collegium Basilea, 2024)
Live streaming technology has created a new career called e-commerce anchors in the ever-changing world of e-commerce. These anchors play an important role in promoting products and promoting e-commerce expertise. This paper examines the precise e-commerce anchor attributes that most successfully influence purchase intentions, including competence, charm, credibility, communication, fame, affinity, and promptness. This paper proposes the role of anchor characteristics in an e-commerce success (RACE) algorithm to identify key characteristics of e-commerce anchors that have a major impact on purchase intention. The results demonstrate that characteristics such as Affinity, Promptness, and Communication have the greatest effects on changing consumer intentions and increasing purchase intentions. This paper highlights the important role of providing practical information on customer behavior, customer engagement, and e-commerce marketers and advertisers in optimizing these attributes for e-commerce success.